2013
DOI: 10.1007/s12041-013-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci associated with yield and yield components under reproductive stage salinity stress in rice (Oryza sativa L.)

Abstract: Salinity tolerance in rice is critical at reproductive stage because it ultimately determines grain yield. An F2 mapping population derived from a Sadri/FL478 cross was exposed to saline field conditions (6-8 dS m(-1)) after the active tillering stage to identify reproductive stage specific QTLs for salinity tolerance. Genetic linkage map was constructed using 123 microsatellite markers on 232 F2 progenies. Totally 35 QTLs for 11 traits under salinity stress were detected with LOD > 3, out of which 28 QTLs tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 40 publications
3
57
0
Order By: Relevance
“…In recent years, QTL analysis in rice helped in mapping several QTLs related to several characters correlated with salinity: QTLs mapped on chromosome 1 and 2 for shoot growth [102]; 5 major QTLs: qRL-7 for root length, qDWRO-9a and qDWRO-9b for dry weight root, qBI-1a and qBI-1b for biomass [103]. Separate QTLs being identified each for sodium uptake, potassium uptake, and sodium:potassium selectivity [104]; 8 QTLs accounting each of three for three traits of the shoots, and each of five for four traits of the roots at five chromosomal regions [105] and many more. A total of 35 QTLs were identified by [106] in an F2 mapping population derived from a Sadri/FL478 cross, the major QTL clusters being mapped in chromosomes 2, 4 and 6 for multiple traits under salinity stress.…”
Section: Response At Molecular Level: Targeted Approach and Cellular mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, QTL analysis in rice helped in mapping several QTLs related to several characters correlated with salinity: QTLs mapped on chromosome 1 and 2 for shoot growth [102]; 5 major QTLs: qRL-7 for root length, qDWRO-9a and qDWRO-9b for dry weight root, qBI-1a and qBI-1b for biomass [103]. Separate QTLs being identified each for sodium uptake, potassium uptake, and sodium:potassium selectivity [104]; 8 QTLs accounting each of three for three traits of the shoots, and each of five for four traits of the roots at five chromosomal regions [105] and many more. A total of 35 QTLs were identified by [106] in an F2 mapping population derived from a Sadri/FL478 cross, the major QTL clusters being mapped in chromosomes 2, 4 and 6 for multiple traits under salinity stress.…”
Section: Response At Molecular Level: Targeted Approach and Cellular mentioning
confidence: 99%
“…In order to cope up with the upcoming photo-inhibitory effects plants undergo modification in their metabolic pathways such as heat debauchery by the xanthophyll pigments and electron transfer to oxygen acceptors (not water) which can result in the formation of ROS (reactive oxygen species). The later response is however mitigated by an initiation of the up regulation of several regulatory enzymes for such as superoxide dismutase, ascorbate peroxidase, catalase, and the various peroxidases [105][106][107][108][109]. The enzymatic antioxidant defense system of plants is inclusive of Superoxide dismutase (SODs), peroxidases, Catalases, and the enzymes of the ascorbate-glutathione cycle: Ascorbate peroxidase (APX), Monodehydro-ascorbate reductase (MDHAR), Dehydro-ascorbate reductase (DHAR), and Glutathionereductase (GR) while non-enzymatic antioxidants include: Ascorbate (AsA) and Glutathione (GSH) [110,111].…”
Section: Defense System Of Rice Against Salinity Stressmentioning
confidence: 99%
“…Rice, one of the primary food crops, is salt sensitive with a threshold of 3 dS m -1 soil electrical conductivity (EC) and a 12 % yield reduction per dS m -1 has been reported above this EC level (Mohammadi et al 2013). Even though soil salinity affects all growth and developmental stages of rice, it depresses grain yield the most seriously if plants are exposed to stress during the reproductive stages.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, screening for salt stress responses and tolerance abilities at the reproductive stage to identify tolerant lines is crucial (Surekha Rao et al 2013). Soil salinity negatively impacts number of tillers per plant, the number of spikelets per panicle, besides the length of panicles as well as number of primary branches per panicle, as pointed out by Mohammadi et al (2013). Soil salinity not only reduces the rice yield substantially but also adversely affects the grain quality.…”
Section: Introductionmentioning
confidence: 99%
“…The locus RM292 on chromosome 1 was located within the region of qKLV-1.1 (Pandit et al 2010); RM213 on chromosome 2 was located within the region of QSst2 (Zang et al 2008); RM539 on chromosome 6 was located within the region of qDRW6 (Wang et al 2012a, b), qDTF6.1 s (Mohammadi et al 2013) and QSkc6 (Zang et al 2008) simultaneously; RM1287 on chromosome 1 was the same marker for Saltol (Mohammadi-Nejad et al 2008), and located within the region of qSKC-1 (Lin et al 2004) and qSNC1 (Thomson et al 2010); RM1379 on chromosome 2 was mapped together with three QTLs (i.e. qPH2, qRKC2 and qCHL2), flanked by SSR markers RM13197 and RM6318 (Thomson et al 2010), and located within the region for salt tolerance reported by Sabouri et al (2009) and Wang et al (2011) simultaneously; RM551 on chromosome 4 and RM281 on chromosome 8 shared the same marker for salt tolerance reported by Mohammadi et al (2013) and Ammar et al (2009); Remarkably, RM1324 on chromosome 3 and RM418 on chromosome 7 associated with both salt-tolerance-related traits (SDS and SKN) at the seedling stage in this study, were also associated with salt tolerance at the germination and early seedling stage in our previous study (Zheng et al 2014), and there were no reports to date for salt tolerance in other studies, suggesting that they were novel markers associated with salt tolerance. Therefore, the markers for salt tolerance mentioned above, which were detected in different mapping populations, different growth period and various environments, were significant markers for salt tolerance in rice.…”
Section: Comparison Of Qtls For Salt Tolerance With Previous Reportsmentioning
confidence: 99%